Pengaruh Media Interaktif Educaplay untuk Meningkatkan Minat Belajar Siswa pada Pelajaran Matematika Siswa Kelas IV MI Ma'arif NU 5 Sekampung - Risky Nur Azizah; Muhammad Ngali Zainal Makmun; Lutfi Fadilah (EQUALS: Jurnal Ilmiah Pendidikan Matematika, 2026)
This study examines the effect of the interactive learning media Educaplay on students’ interest in learning mathematics at the fourth-grade level of MI Ma’arif NU 5 Sekampung. The study is grounded in the issue of low student interest caused by monotonous and less interactive teaching methods. The objective of this research is to determine whether the use of Educaplay significantly influences students’ learning interest. This research employs a quantitative approach with a quasi-experimental design involving 21 students selected through total sampling. The research design used is Non-Equivalent Control Group Design. Data were collected using questionnaires, observations, and documentation, while data analysis was conducted using validity, reliability, normality, and independent sample t-test. The findings reveal that the use of Educaplay has a significant effect on students’ learning interest, as indicated by a significance value of 0.001 (<0.05). The results also show improvements in students’ attention, participation, enthusiasm, and overall engagement in learning mathematics. The novelty of this study lies in the application of interactive digital media specifically in the context of Madrasah Ibtidaiyah, focusing on learning interest rather than cognitive outcomes. This study implies that integrating interactive media into mathematics learning can enhance student engagement and create a more meaningful learning experience.